Break-junction experiments on the Kondo semiconductor CeNiSn: tunnelling versus direc: Электpонные свойства металлов и сплавов - Naidyuk, Yu. G.; Gloos, K.; Takabatake, T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
We have investigated the rare-earth Kondo semiconductor CeNiSn by point contact and tunneling spectroscopy using mechanically controllable break junctions. I(V) characteristics and their derivatives were recorded for contacts from the metallic to the tunneling regime at temperatures between 0.1-8 K and in magnetic fields up to 8 T. We found that CeNiSn behaves like a compound with typical metallic properties instead of the expected semiconducting behavior. The main spectral feature is a pronounced zero-bias conductance minimum of about 10 meV width, which appears to be of magnetic nature. These break-junction experiments provide no clear-cut evidence for an energy (pseudo)gap of CeNiSn.